New records of two sponge-associated species of Upogebia Leach, 1814 from southern India (Decapoda: Gebiidea: Upogebiidae): U. hexaceras (Ortmann, 1894) and U. nithyanandan (Sakai, Türkay & Al Aidaroos, 2015) resurrected from the synonymy of U. balmaorum Ngoc-Ho, 1990 - Komai, Tomoyuki; Ravinesh, Raveendhiran; Riyas, Abdul; Kumar, Appukuttannair Biju (Zootaxa, 2020)
Two species of the mud shrimp genus Upogebia Leach, 1814 (Gebiidea: Upogebiidae) are recorded from India for the first time based on material from Tamil Nadu: U. hexaceras (Ortmann, 1894) and U. nithyanandan (Sakai, Türkay & Al Aidaroos, 2015). Both were found in burrows in an unidentified sponge. Upogebia nithyanandan is resurrected as a valid species from the synonymy of U. balmaorum Ngoc-Ho, 1990, recently proposed by Dworschak & Poore (2018). The two species are fully described and illustrated on the basis of the newly collected specimens, and diagnostic characters for species recognition are discussed.